Sejarah Desa Tebas Sungai Kecamatan Tebas Kabupaten Sambas Tahun 1938-2024 - Damai Damai; Tomi Tomi; Beti Yanuri Posha (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Tebas Sungai Village is one of the villages in Tebas District, which has a very unique history and has experienced development from its formation until now, and is the oldest village, especially in Tebas District with a large population, and a high level of education. This research aims to explore what events were behind the formation of Tebas Sungai Village, know the development of Tebas Sungai Village from 1938-2024, and find out various aspects of the life of the people of Tebas Sungai Village, which include social, religious, economic, political, cultural and educational aspects. This type of research is qualitative research using critical analysis. The approaches used are historical, sociological, and anthropological approaches. Meanwhile, the data sources obtained are from primary and secondary sources. The data that has been collected is processed and analyzed through the stages of historical research methods, namely the heuristic, verification, interpretation, and historiography stages. The data collection techniques in this study include observation, interviews, and documentation. The results of the study show that (1) The formation of Tebas Sungai Village, Tebas District cannot be separated from the long history that began with the event of land clearing around the Tebas River by Sultan Muhammad Tsafiuddin I (1632-1668). (2) The development of Tebas Sungai Village from the colonial period, the beginning of independence, the old order of the new order to the reform, until the expansion of Sambas Regency.experienced significant changes and developments, especially in infrastructure, development, and community welfare.